PEMBERDAYAAN MASYARAKAT DESA MAMAN MELALUI PELATIHAN PEMBUATAN DIMSUM SIOMAY BAGI KELOMPOK PKK - Hermanto, Koko; Mashabai, Ismi; Hudaningsih, Nurul; Utami, Silvia Firda; Turrahmi, Ulfa (Universitas Mataram, 2025)
The problem of stunting in West Nusa Tenggara (NTB) remains a serious concern despite a significant decline in stunting rates. Despite this considerable decline, NTB has yet to reach the national target of 14%. There is still 10.6% left to achieve to meet the national target. Stunting in NTB is caused by chronic, recurring malnutrition, especially in animal protein. Therefore, to meet these nutritional needs and increase children's appetite, innovations in stunting management are needed, one of which is creating contemporary foods such as dimsum siomay. Training on making dimsum siomay using chicken and shrimp as raw materials was provided to the Family Welfare Empowerment (PKK) group in Maman Village, Sumbawa Regency, to improve the knowledge and economy of its members, and to reduce stunting rates. The training method used was the Participatory Rural Appraisal approach, which included the delivery of materials and hands-on practice in making dimsum siomay. A review of the training activities was conducted after the training, aiming to evaluate the effectiveness of the training in improving the knowledge, skills, and awareness of the PKK women's group in Maman Village in developing culinary businesses. The evaluation results showed a significant increase in the knowledge, skills, and caring attitudes of PKK members after the training. The training also raised PKK members' awareness of developing independent and sustainable culinary businesses. The training's effectiveness rate was 45%, categorized as quite effective in empowering the PKK women's group economically, and can serve as a model for other community empowerment programs.